Development and clinical evaluation of a CRISPR/Cas13a-based diagnostic test to detect Mycobacterium tuberculosis in clinical specimens - Ren, Weicong; Zhou, You; Li, Haoran; Shang, Yuanyuan; Zhang, Xuxia; Yuan, Jinfeng; Li, Shanshan; Li, Chuanyou; Pang, Yu (Frontiers in Microbiology, 2023)
Objective: Tuberculosis diagnosis requires rapid, simple and highly sensitive methods. Clustered regularly interspaced short palindromic repeats (CRISPRs) and associated protein (Cas) systems are increasingly being used for clinical diagnostic applications, due to their high flexibility, sensitivity and specificity. We developed a sensitive Mycobacterium tuberculosis (MTB) complex polymerase chain reaction (PCR)-CRISPR/Cas13a detection method (CRISPR-MTB) then evaluated its performance in detecting MTB in clinical specimens. Methods: The conserved MTB IS1081 sequence was used to design CRISPR-derived RNAs (crRNAs) and T7 promotor sequencing-containing PCR primers for use in the CRISPR-MTB assay then assay performance was evaluated using 401 clinical specimens. Results: The CRISPR-MTB assay provided a low limit of detection of 1 target sequence copy/μL and excellent specificity. Furthermore, use of the assay to detect MTB in bronchioalveolar lavage fluid (BALF), sputum and pus samples provided superior sensitivity (261/268, 97.4%) as compared to sensitivities of acid-fast bacilli (130/268, 48.5%) and mycobacterial culture (192/268, 71.6%) assays, and comparable or greater sensitivity to that of GeneXpert MTB/RIF (260/268, 97.0%). Conclusion: The CRISPR-MTB assay, which provides excellent sensitivity and specificity for MTB detection in sputum, BALF and pus samples, is a viable alternative to conventional tests used to diagnose TB in resource-limited settings.